GunungHub – Guide and Reservation Online Application - Nor Azman, Amir Asyraaf; Mohd. Yasin, Suhaila (Applied Information Technology And Computer Science, 2023)
Most hikers in Malaysia find it challenging to join hiking trips and identify climbable mountains. The current method for joining a hiking expedition is complicated. At present, advertising trips and making reservations are not systematic and time-consuming. Further, it is difficult to handle trip booking information by numerous participants. Thus, a system is developed that incorporates all of the essential operations and information into a single web application. The database used makes booking management and mountain information more efficient. Customers may learn about the trip and make bookings in a structured manner. Errors between administration and customers are minimal. The system was developed using an object-oriented approach, with the prototype model as the development model. The system was developed using the Laravel framework. This system improves the efficiency of current procedures in booking management. This methodology will assist both the climbing community and the organization by providing a systematic way.